Given that f(x) = −x + 4 and g(x) = −2x − 3, solve for f(g(x)) when x = 2. 1. -14 2.-7 3.7 4.11

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

Given that f(x) = −x + 4 and g(x) = −2x − 3, solve for f(g(x)) when x = 2. 1. -14 2.-7 3.7 4.11

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

first step is to solve g(x) when x = 2 then take the result and plug it into f(x)
Do I divide 2 to -2x and -3? @Vocaloid
... huh? let's take it one step at a time: what is g(x) when x = 2?

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

okay so g(2)=-2x-3 what do I do next with this funtion? @Vocaloid
plug in 2 for x and tell me what you get when you solve it
I'm a bit unsure if it's right but negative 7
yup! g(2) = -7 alright, so now let's plug in -7 for x using f(x)
f(-7)=-4(-7)=9 I'm I wrong at some part? @Vocaloid
uh, not quite f(x) = -x+4, remember?
if x = -7, what is f(x)?
oh that was my fault I plugged it in for the wrong problem @Vocaloid
instead of the x it would be F(-7) Am I right? @Vocaloid
yup, so what is our answer? :)
F(-7)=-7+4 F(-7)=-3 what am I going to use F(-7) for? @Vocaloid
not quite, check your math again f(-7) = -(-7) + 4 = ?
F(-7)=-7+4 F(-7)=-3 F(g(2))=-7 right? :) @vocaloid
uh... not quite... what is -(-7)?
hint: -(-a) = a
the answer for g(x) function
no, can you please answer my question? -(-7) = ? hint: -(-a) = a
I do not know
I'm a bit slow right now sorry
well, ok, we know that f(-7) = -(-7) + 4, right? -(-7) = 7, so f(x) = 7 + 4 = 11 11 is our answer
full explanation: the question asked for f(g(x)) when x = 2 that means, plug in 2 for x to find g(2) g(2) = -7, so we plug in -7 for x in f(x) f(-7) = 11, meaning f(g(2)) = 11
but how did you get that negative in front of the perentheses
f(x) = -x+4 x = -7 f(x) = -(-7) + 4
oh so the negative of the other x was still be in play
yup!
that's what i was missing hahah:) i might be a dumbarse but thanks a lot you're a really good helper :)

Not the answer you are looking for?

Search for more explanations.

Ask your own question